UJI TOKSISITAS MENGGUNAKAN METODE BSLT DAN SKRINING FITOKIMIA EKSTRAK (Melastoma malabathricum L.) - Lia Fikayuniar; Ermi Abriyani; Fioren Irwandira; Sinta Bela; Sartika Dewi (Jurnal Buana Farma, 2022)
Melastoma malabathricum L. plant or commonly known as senduduk is often used as a source of food and medicine. The stem of senduduk is one part of the senduduk plant that has not been widely utilized in existence compared to its flowers, fruits and leaves. Senduduk plant has activity as antidiarrhea, fractures, digestive tract disorders, melancholy, seizures, epilepsy, abdominal pain, thrush, anti-inflammatory, antipyretic, wound, and antioxidant, in addition to the myriad benefits of M. malabathricum L. also contains toxic compounds. Therefore, this study aims to determine the toxic activity of n-hexane extract, ethyl acetate, senduduk stem methanol (M. malabathricum L.) against A. salina L. shrimp larvae to avoid toxic risks in humans. The method used in the study was the Brine Shrimp Lethality Test (BSLT) using 10 shrimp larvae A. salina L. in each replication carried out three times afterwards followed by probit analysis to see the percentage of shrimp larva death. The study also found results that n-Hexane extract contains flavonoids, quinones and saponins, while ethyl acetate and methanol extracts contain only flavonoids and quinone. Senduduk stem extract (M. malabathricum L.) has a toxic effect with a value of LC50 < 1000 ppm or in the n-Hexane extract of 1.66 ppm, while in ethyl acetate extract of 56.23 ppm and methanol extract of 128.82 ppm.